2002
DOI: 10.1152/ajpcell.00390.2001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium on myosin thick filament formation in intact airway smooth muscle

Abstract: Myosin thick filaments have been shown to be structurally labile in intact smooth muscles. Although the mechanism of thick filament assembly/disassembly for purified myosins in solution has been well described, regulation of thick filament formation in intact muscle is still poorly understood. The present study investigates the effect of resting calcium level on thick filament maintenance in intact airway smooth muscle and on thick filament formation during activation. Cross-sectional density of the thick fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 13 publications
(22 reference statements)
2
47
2
Order By: Relevance
“…Thus actin filament formation may be a component in the activation of contraction, which might also play a role in the phenomena studied here, because the portal vein has a prominent myogenic tone that is clearly sensitive to stretch (17). Recent evidence also indicates that thick (myosin) filament assembly may be promoted by con- tractile activation and that this mechanism is most pronounced in smooth muscles with low myogenic tone, suggesting that maintained tone contributes to the preservation of filament organization (14). The present results show that stretch and altered actin dynamics both influence cell differentiation via mechanisms that have much in common.…”
Section: Discussionmentioning
confidence: 69%
“…Thus actin filament formation may be a component in the activation of contraction, which might also play a role in the phenomena studied here, because the portal vein has a prominent myogenic tone that is clearly sensitive to stretch (17). Recent evidence also indicates that thick (myosin) filament assembly may be promoted by con- tractile activation and that this mechanism is most pronounced in smooth muscles with low myogenic tone, suggesting that maintained tone contributes to the preservation of filament organization (14). The present results show that stretch and altered actin dynamics both influence cell differentiation via mechanisms that have much in common.…”
Section: Discussionmentioning
confidence: 69%
“…By examining the details of length-dependent properties of ASM, including adapted and nonadapted isometric force, shortening velocity, power output, rate of adenosine tiphosphate utilisation and change in myosin filament density (or filament mass), KUO et al [188], QI et al [192] and HERRERA and co-workers [192][193][194][195] have provided evidence that length adaptation in ASM involves changes in the number of contractile units in series and in parallel. They also showed that externally applied strain on ASM in the relaxed state led directly to partial disassembly of the myosin filaments [168], thus providing an explanation for the strain-induced inhibition of muscle force, which could underlie the phenomenon of deepinspiration-induced bronchoprotection, as discussed in the previous section.…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 99%
“…Tissue samples were prepared for electron microscopy as previously described (Kuo et al, 2001;Herrera et al, 2002). Briefly, muscle preparations were fixed for 15 minutes while they were still attached to the experiment apparatus.…”
Section: Muscle Preparationsmentioning
confidence: 99%
“…The final muscle contraction was induced by addition to the muscle bath 0.1 mM of acetylcholine to ensure continued activation during fixation. Muscle strips were fixed at the plateau of contraction (120 seconds after stimulation) while they were still attached to the experiment apparatus (Herrera et al, 2002;Qi et al, 2002) and force generated by the muscle was monitored throughout the period of initial fixation (15 minutes). In the contracted muscles, after reaching a force peak, there was a small decline in force (<5% maximal force) during fixation.…”
Section: Elasticity Of the Nuclear Envelopementioning
confidence: 99%